2021
DOI: 10.1038/s41598-021-86870-3
|View full text |Cite
|
Sign up to set email alerts
|

A derivative of vitamin B3 applied several days after exposure reduces lethality of severely irradiated mice

Abstract: Most, if not all, of the hitherto tested substances exert more or less pronounced pro-survival effects when applied before or immediately after the exposure to high doses of ionizing radiation. In the present study we demonstrate for the first time that 1-methyl nicotinamide (MNA), a derivative of vitamin B3, significantly (1.6 to 1.9 times) prolonged survival of BALB/c mice irradiated at LD30/30 (6.5 Gy), LD50/30 (7.0 Gy) or LD80/30 (7.5 Gy) of γ-rays when the MNA administration started as late as 7 days post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…These prosurvival effects might be related to the anti-inflammatory and/or antithrombotic properties of the vitamin B3 derivatives and do not seem to be mediated by stimulation of hematopoiesis. These results show that MNA may represent a prototype of a radiomitigator because it reduces the severity and/or progression of radiation-induced injuries when applied several hours or days after exposure to high doses of IR [184].…”
Section: Vitaminsmentioning
confidence: 78%
“…These prosurvival effects might be related to the anti-inflammatory and/or antithrombotic properties of the vitamin B3 derivatives and do not seem to be mediated by stimulation of hematopoiesis. These results show that MNA may represent a prototype of a radiomitigator because it reduces the severity and/or progression of radiation-induced injuries when applied several hours or days after exposure to high doses of IR [184].…”
Section: Vitaminsmentioning
confidence: 78%
“…We identified specific metabolites and pathways associated with recurrent participants, non-recurrent participants, or both.The metabolites identified in the non-recurrent patients include: methylnicotinamide, a metabolite of the class of nicotinamides (NAD + ) and most species, including humans and Plasmodium can produce NAD + 35 , 36 . Previous studies on Plasmodium species reported high NAD + levels during malaria, with infected erythrocytes having 5 to tenfold higher concentrations compared to the uninfected red blood cells 31 , 32 . In a malaria challenge study, methylnicotinamide was demonstrated to be of variable importance upon P. falciparum infection, being significantly higher among the Europeans than the Africans 37 .…”
Section: Discussionmentioning
confidence: 89%
“…In addition, we observed that the abundance of diamino-hydroxy-methylformamidopyrimidine was reduced with significant difference at D90 compared to D0, during the active vivax malaria, before the treatment. Almost all the metabolites annotated were either amino acids or their intermediates except methylnicotinamide which is a form of vitamin B3 31 (Fig. 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these discrepancies in miRNA expression between the sensitive and resistant strains have potential to predict who is more likely to require urgent care vesus routine follow-up. Further, differences in relative resistance as determined by reported LD50/30 for each strain may explain the difficulty in differentiating miRNAs altered at 1 Gy, 2 Gy, 4 Gy (viable) vs. 8 Gy (high risk) but allow for differentiation between low dose (1 and 2 Gy) compared to high dose (4 Gy and 8 Gy) (66)(67)(68)(69). After a 4 Gy dose, BALB/c mice may already be succumbing to radiation injury, while C3H/HeJ and C57BL/6 are surviving.…”
Section: Discussionmentioning
confidence: 99%